Magical Thinking - Conrod, Heidi Jill (Université d'Ottawa / University of Ottawa, 2016)
In Magical Thinking, Heidi Conrod explores through the act of painting, the depiction of mental states through the cautious release and withholding of visual, conceptual, and autobiographical cues. Reflecting on the nature of memory and time and the fluid ways in which these seemingly immaterial phenomena interact, the paintings represent multiple visions within one viewing experience; commenting not only on the surface of things, but also on what may lie hidden beneath. The works are best understood through introspection rather than a forced rationale. These paintings are intended to read like a stream, or perhaps a pool of consciousness, where the unconscious is expressed through swirls of imagery with surrealist undertones alluding to the seemingly contradictory conditions of dream and reality. Here fact, fiction, memory and imagination, are intertwined in a non-linear style through a multitude of painterly applications.
Keywords: painting; surrealism